2 kkyykkylyllyllylykkykylykkkjjjkkl
Answer:
MB = 26
Step-by-step explanation:
AM = 2x - 3
MB = 5x + 1
AB = 21 - (-12)
= 21 + 12
= 33
According to the question M is between A and B. So,
![\rm \longrightarrow AB = AM + MB \\ \\ \rm \longrightarrow 33 = (2x - 3) + (5x + 1) \\ \\ \rm \longrightarrow 2x - 3 + 5x + 1 = 33 \\ \\ \rm \longrightarrow (2x + 5x) + (1 - 3) = 33 \\ \\ \rm \longrightarrow 7x - 2 = 33 \\ \\ \rm \longrightarrow 7x - 2 + 2 = 33 + 2 \\ \\ \rm \longrightarrow 7x = 35 \\ \\ \rm \longrightarrow \dfrac{7}{7} x = \dfrac{35}{7} \\ \\ \rm \longrightarrow x = 5](https://tex.z-dn.net/?f=%20%5Crm%20%5Clongrightarrow%20AB%20%3D%20AM%20%2B%20MB%20%5C%5C%20%20%5C%5C%20%20%5Crm%20%5Clongrightarrow%2033%20%3D%20%282x%20-%203%29%20%2B%20%285x%20%2B%201%29%20%20%5C%5C%20%20%5C%5C%20%20%5Crm%20%5Clongrightarrow%202x%20-%203%20%2B%205x%20%2B%201%20%3D%2033%20%5C%5C%20%20%5C%5C%20%20%5Crm%20%5Clongrightarrow%20%282x%20%2B%205x%29%20%2B%20%281%20-%203%29%20%3D%2033%20%5C%5C%20%20%5C%5C%20%20%5Crm%20%5Clongrightarrow%207x%20-%202%20%3D%2033%20%5C%5C%20%20%5C%5C%20%20%5Crm%20%5Clongrightarrow%207x%20-%202%20%2B%202%20%3D%2033%20%2B%202%20%5C%5C%20%20%5C%5C%20%20%5Crm%20%5Clongrightarrow%207x%20%3D%2035%20%5C%5C%20%20%5C%5C%20%20%5Crm%20%5Clongrightarrow%20%20%5Cdfrac%7B7%7D%7B7%7D%20x%20%3D%20%20%5Cdfrac%7B35%7D%7B7%7D%20%20%5C%5C%20%20%5C%5C%20%20%5Crm%20%5Clongrightarrow%20x%20%3D%205)
Value of MB = 5 × 5 + 1
= 25 + 1
= 26
Answer:
x^2-4x+y^2+6y-108=0
Step-by-step explanation:
![The- equation- of- circle- with -center- at- (h,k) -and -a -radius- of- r -is: \\(x-h)^2 +(y-k)^2 = r^2\\h = 2 , \\ k = -3\\r = 11\\(x-2)^2+(y-(-3))^2 = 11^2\\(x-2)^2+(y+3)^2 = 121\\x^2-4x+4 +y^2+6y+9 = 121\\x^2 -4x+y^2+6y+4+9=121\\x^2 -4x+y^2+6y+13=121\\x^2 -4x+y^2+6y=121-13\\x^2 -4x+y^2+6y= 108\\x^2 -4x+y^2+6y-108 = 0](https://tex.z-dn.net/?f=The-%20equation-%20of-%20circle-%20with%20-center-%20at-%20%28h%2Ck%29%20-and%20-a%20-radius-%20of-%20r%20-is%3A%20%5C%5C%28x-h%29%5E2%20%2B%28y-k%29%5E2%20%3D%20r%5E2%5C%5Ch%20%3D%202%20%2C%20%5C%5C%20%20k%20%3D%20-3%5C%5Cr%20%3D%2011%5C%5C%28x-2%29%5E2%2B%28y-%28-3%29%29%5E2%20%3D%2011%5E2%5C%5C%28x-2%29%5E2%2B%28y%2B3%29%5E2%20%3D%20121%5C%5Cx%5E2-4x%2B4%20%2By%5E2%2B6y%2B9%20%3D%20121%5C%5Cx%5E2%20-4x%2By%5E2%2B6y%2B4%2B9%3D121%5C%5Cx%5E2%20-4x%2By%5E2%2B6y%2B13%3D121%5C%5Cx%5E2%20-4x%2By%5E2%2B6y%3D121-13%5C%5Cx%5E2%20-4x%2By%5E2%2B6y%3D%20108%5C%5Cx%5E2%20-4x%2By%5E2%2B6y-108%20%3D%200)
Answer:
g) x = 30
h) x = 30
i) m = 55
j) x = 24
k) k = 45
Step-by-step explanation:
G)
all angles of a triangle add up to 180.
the square in the bottom right of the triangle is 90 btw
2x + x + 90 = 180
3x + 90 = 180
3x + 90 - 90 = 180 - 90
3x = 180 - 90
3x = 90
3x/3 = 90/3
x = 30
H)
this is an Isosceles triangle.
that means the bottom two angles are equal.
75 + 75 + x = 180
x + 150 = 180
x + 150 - 150 = 180 - 150
x = 180 - 150
x = 30
I)
2m is supplementary to the bottom right angle of the triangle.
that means they add together to make 180.
80 + 30 + (180 - 2m) = 180
110 - 2m = 180 - 180
110 - 2m = 0
110 = 2m
110/2 = m
55 = m
J)
to save time I'm not going to write out the steps, its the same as the i.
2x + 3x + (180 - 120 ) = 180
5x + 60 = 180
5x = 180 - 60
5x = 120
x = 120/5
x = 24
K)
imagine this as a triangle and a square.
sorry I'm not sure how to explain this -.-
but the equation would be
k + k + 90 = 180
2k + 90 = 180
2k = 180 - 90
2k = 90
k = 45
L)
Im not sure how to solve this, I'm sorry :( hope you figure it out!
Answer:
Li Jing's formula i.e.
is right.
Step-by-step explanation:
Considering the sequence
![-5,\:-25,\:-125,\:-625,...](https://tex.z-dn.net/?f=-5%2C%5C%3A-25%2C%5C%3A-125%2C%5C%3A-625%2C...)
A geometric sequence has a constant ratio r and is defined by
![g_n=g_0\cdot r^{n-1}](https://tex.z-dn.net/?f=g_n%3Dg_0%5Ccdot%20r%5E%7Bn-1%7D)
![\mathrm{Compute\:the\:ratios\:of\:all\:the\:adjacent\:terms}:\quad \:r=\frac{g_{n+1}}{g_n}](https://tex.z-dn.net/?f=%5Cmathrm%7BCompute%5C%3Athe%5C%3Aratios%5C%3Aof%5C%3Aall%5C%3Athe%5C%3Aadjacent%5C%3Aterms%7D%3A%5Cquad%20%5C%3Ar%3D%5Cfrac%7Bg_%7Bn%2B1%7D%7D%7Bg_n%7D)
![\frac{-25}{-5}=5,\:\quad \frac{-125}{-25}=5,\:\quad \frac{-625}{-125}=5](https://tex.z-dn.net/?f=%5Cfrac%7B-25%7D%7B-5%7D%3D5%2C%5C%3A%5Cquad%20%5Cfrac%7B-125%7D%7B-25%7D%3D5%2C%5C%3A%5Cquad%20%5Cfrac%7B-625%7D%7B-125%7D%3D5)
![\mathrm{The\:ratio\:of\:all\:the\:adjacent\:terms\:is\:the\:same\:and\:equal\:to}](https://tex.z-dn.net/?f=%5Cmathrm%7BThe%5C%3Aratio%5C%3Aof%5C%3Aall%5C%3Athe%5C%3Aadjacent%5C%3Aterms%5C%3Ais%5C%3Athe%5C%3Asame%5C%3Aand%5C%3Aequal%5C%3Ato%7D)
![r=5](https://tex.z-dn.net/?f=r%3D5)
So, the sequence is geometric.
as
![\mathrm{The\:first\:element\:of\:the\:sequence\:is}](https://tex.z-dn.net/?f=%5Cmathrm%7BThe%5C%3Afirst%5C%3Aelement%5C%3Aof%5C%3Athe%5C%3Asequence%5C%3Ais%7D)
![g_1=-5](https://tex.z-dn.net/?f=g_1%3D-5)
![r=5](https://tex.z-dn.net/?f=r%3D5)
so
![g_n=g_1\cdot r^{n-1}](https://tex.z-dn.net/?f=g_n%3Dg_1%5Ccdot%20r%5E%7Bn-1%7D)
![\mathrm{Therefore,\:the\:}n\mathrm{th\:term\:is\:computed\:by}\:](https://tex.z-dn.net/?f=%5Cmathrm%7BTherefore%2C%5C%3Athe%5C%3A%7Dn%5Cmathrm%7Bth%5C%3Aterm%5C%3Ais%5C%3Acomputed%5C%3Aby%7D%5C%3A)
![g_n=-5\cdot \:5^{n-1}](https://tex.z-dn.net/?f=g_n%3D-5%5Ccdot%20%5C%3A5%5E%7Bn-1%7D)
Therefore, Li Jing's formula i.e.
is right.